2014
DOI: 10.1080/15374416.2013.873985
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Associations Between Interpersonal and Values Dimensions of School Climate and Peer Victimization in Elementary School Children

Abstract: We examine longitudinal relations among children's and parents' reports of peer victimization and their perceptions of school climate dimensions reflecting school interpersonal relationships (relationships among children and their teachers and peers, and of parents and principals) and values (fairness and equity of access to resources). Children were in Grades 3 and 4 at Time 1 (Mage = 9.32, SDage = .74; 49% boys). Bidirectional influences of school climate and reports of peer victimization were investigated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 47 publications
3
33
2
3
Order By: Relevance
“…There is a need to expand this ecological view of school climate to clarify targets for improving the safety of our schools (Manvell, 2012) and the impact of positive school climate on child outcomes. Consistent with a growing body of research (Espelage et al, 2014;Leadbeater et al, 2014;Wang et al, 2014), our findings suggest that working to improve school relationships between students and teacher and students themselves, and to enhance students' experiences of fairness and equity in sharing resources may be key to improving children's social, emotional, and behavioral outcomes. Active responses on the part of school staff that support victimized children and their families are crucial to stop the escalating negative school climate perceptions that can preoccupy withdrawn children who may feel marginalized from school activities.…”
Section: Limitations and Conclusionsupporting
confidence: 81%
See 3 more Smart Citations
“…There is a need to expand this ecological view of school climate to clarify targets for improving the safety of our schools (Manvell, 2012) and the impact of positive school climate on child outcomes. Consistent with a growing body of research (Espelage et al, 2014;Leadbeater et al, 2014;Wang et al, 2014), our findings suggest that working to improve school relationships between students and teacher and students themselves, and to enhance students' experiences of fairness and equity in sharing resources may be key to improving children's social, emotional, and behavioral outcomes. Active responses on the part of school staff that support victimized children and their families are crucial to stop the escalating negative school climate perceptions that can preoccupy withdrawn children who may feel marginalized from school activities.…”
Section: Limitations and Conclusionsupporting
confidence: 81%
“…Past research has also shown that more vulnerable children may have experiences at school that affect their general beliefs about relationships with their peers and teachers (and hence their school climate ratings). For example, children who experience higher levels of peer rejection and aggression over time come to believe that their peers may not be trustworthy (Ladd et al, 2014) and victimized children hold more negative views of school climate (Leadbeater et al, 2014;Nickerson et al, 2014). Chronic victimization may leave children feeling that their experiences are normative across the school population and reduce the likelihood that they will seek help.…”
Section: Differential Associations With Peer Victimization and Mentalmentioning
confidence: 94%
See 2 more Smart Citations
“…Leadbeater, Sukhawathanakul, Smith, and Bowen (2014) conducted a study to examine the prospective relations among peer victimization measures and children's perceptions of school climate dimensions (e.g., equity of access to resources within the school) in Canadian schools. The authors examined and found evidence for bidirectional associations between school climate dimensions and peer victimization.…”
mentioning
confidence: 99%